Reducing Tobacco-Related Cancer Incidence and Mortality: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
Tobacco use is the leading cause of preventable death in United States, causing more than 440,000 deaths annually and resulting in $193 billion in health-related economic losses each year—$96 billion in direct medical costs and $97 billion in lost productivity. Since the first U.S. Surgeon General's report on smoking in 1964, more than 29 Surgeon General's reports, drawing on data from thousands of studies, have documented the overwhelming and conclusive biologic, epidemiologic, behavioral, and pharmacologic evidence that tobacco use is deadly. This evidence base links tobacco use to the development of multiple types of cancer and other life-threatening conditions, including cardiovascular and respiratory diseases. Smoking accounts for at least 30 percent of all cancer deaths, and 80 percent of lung cancer deaths. Despite the widespread agreement on the dangers of tobacco use and considerable success in reducing tobacco use prevalence from over 40 percent at the time of the 1964 Surgeon General's report to less than 20 percent today, recent progress in reducing tobacco use has slowed. An estimated 18.9 percent of U.S. adults smoke cigarettes, nearly one in four high school seniors smoke, and 13 percent of high school males use smokeless tobacco products. In recognition that progress in combating cancer will not be fully achieved without addressing the tobacco problem, the National Cancer Policy Forum of the Institute of Medicine (IOM) convened a public workshop, Reducing Tobacco-Related Cancer Incidence and Mortality, June 11-12, 2012 in Washington, DC. In opening remarks to the workshop participants, planning committee chair Roy Herbst, professor of medicine and of pharmacology and chief of medical oncology at Yale Cancer Center and Smilow Cancer Hospital, described the goals of the workshop, which were to examine the current obstacles to tobacco control and to discuss potential policy, outreach, and treatment strategies that could overcome these obstacles and reduce tobacco-related cancer incidence and mortality. Experts explored a number of topics, including: the changing demographics of tobacco users and the changing patterns of tobacco product use; the influence of tobacco use on cancer incidence and cancer treatment outcomes; tobacco dependence and cessation programs; federal and state level laws and regulations to curtail tobacco use; tobacco control education, messaging, and advocacy; financial and legal challenges to tobacco control efforts; and research and infrastructure needs to support tobacco control strategies, reduce tobacco related cancer incidence, and improve cancer patient outcomes. Reducing Tobacco-Related Cancer Incidence and Mortality summarizes the workshop.
Keywords: Health and Medicine

Toward Quality Measures for Population Health and the Leading Health Indicators - Institute of Medicine (The National Academies Press, 2013)
The Institute of Medicine (IOM) Committee on Quality Measures for the Healthy People Leading Health Indicators was charged by the Office of the Assistant Secretary for Health to identify measures of quality for the 12 Leading Health Indicator (LHI) topics and 26 Leading Health Indicators in Healthy People 2020 (HP2020), the current version of the Department of Health and Human Services (HHS) 10-year agenda for improving the nation's health. The scope of work for this project is to use the nine aims for improvement of quality in public health (population-centered, equitable, proactive, health promoting, risk reducing, vigilant, transparent, effective, and efficient) as a framework to identify quality measures for the Healthy People Leading Health Indicators (LHIs). The committee reviewed existing literature on the 12 LHI topics and the 26 Leading Health Indicators. Quality measures for the LHIs that are aligned with the nine aims for improvement of quality in public health will be identified. When appropriate, alignments with the six Priority Areas for Improvement of Quality in Public Health will be noted in the Committee's report. Toward Quality Measures for Population Health and the Leading Health Indicators also address data reporting and analytical capacities that must be available to capture the measures and for demonstrating the value of the measures to improving population health. Toward Quality Measures for Population Health and the Leading Health Indicators provides recommendations for how the measures can be used across sectors of the public health and health care systems. The six priority areas (also known as drivers) are population health metrics and information technology; evidence-based practices, research, and evaluation; systems thinking; sustainability and stewardship; policy; and workforce and education.
Keywords: Health and Medicine

Challenges and Opportunities for Change in Food Marketing to Children and Youth: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
The childhood obesity epidemic is an urgent public health problem. The most recent data available show that nearly 19 percent of boys and about 15 percent of girls aged 2-19 are obese, and almost a third of U.S. children and adolescents are overweight or obese (Ogden et al., 2012). The obesity epidemic will continue to take a substantial toll on the health of Americans. In the midst of this epidemic, children are exposed to an enormous amount of commercial advertising and marketing for food. In 2009, children aged 2-11 saw an average of more than 10 television food ads per day (Powell et al., 2011). Children see and hear advertising and marketing messages for food through many other channels as well, including radio, movies, billboards, and print media. Most notably, many new digital media venues and vehicles for food marketing have emerged in recent years, including Internet-based advergames, couponing on cell phones, and marketing on social networks, and much of this advertising is invisible to parents. The marketing of high-calorie, low-nutrient foods and beverages is linked to overweight and obesity. A major 2006 report from the Institute of Medicine (IOM) documents evidence that television advertising influences the food and beverage preferences, requests, and short-term consumption of children aged 2-11 (IOM, 2006). Challenges and Opportunities for Change in Food Marketing to Children and Youth also documents a body of evidence showing an association of television advertising with the adiposity of children and adolescents aged 2-18. The report notes the prevailing pattern that food and beverage products marketed to children and youth are often high in calories, fat, sugar, and sodium; are of low nutritional value; and tend to be from food groups Americans are already overconsuming. Furthermore, marketing messages that promote nutrition, healthful foods, or physical activity are scarce (IOM, 2006). To review progress and explore opportunities for action on food and beverage marketing that targets children and youth, the IOM's Standing Committee on Childhood Obesity Prevention held a workshop in Washington, DC, on November 5, 2012, titled "New Challenges and Opportunities in Food Marketing to Children and Youth."
Keywords: Food and Nutrition

U.S. Health in International Perspective: Shorter Lives, Poorer Health - Institute of Medicine; National Research Council (The National Academies Press, 2013)
The United States is among the wealthiest nations in the world, but it is far from the healthiest. Although life expectancy and survival rates in the United States have improved dramatically over the past century, Americans live shorter lives and experience more injuries and illnesses than people in other high-income countries. The U.S. health disadvantage cannot be attributed solely to the adverse health status of racial or ethnic minorities or poor people: even highly advantaged Americans are in worse health than their counterparts in other, "peer" countries. In light of the new and growing evidence about the U.S. health disadvantage, the National Institutes of Health asked the National Research Council (NRC) and the Institute of Medicine (IOM) to convene a panel of experts to study the issue. The Panel on Understanding Cross-National Health Differences Among High-Income Countries examined whether the U.S. health disadvantage exists across the life span, considered potential explanations, and assessed the larger implications of the findings. U.S. Health in International Perspective presents detailed evidence on the issue, explores the possible explanations for the shorter and less healthy lives of Americans than those of people in comparable countries, and recommends actions by both government and nongovernment agencies and organizations to address the U.S. health disadvantage.
Keywords: Behavioral and Social Sciences; Health and Medicine; Surveys and Statistics

Identifying and Addressing the Needs of Adolescents and Young Adults with Cancer: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
Identifying and Addressing the Needs of Adolescents and Young Adults with Cancer is the summary of a workshop convened by the Institute of Medicine's National Cancer Policy Forum in July 2013 to facilitate discussion about gaps and challenges in caring for adolescent and young adult cancer patients and potential strategies and actions to improve the quality of their care. The workshop featured invited presentations from clinicians and other advocates working to improve the care and outcomes for the adolescent and young adult population with cancer. Cancer is the leading disease-related cause of death in adolescents and young adults. Each year nearly 70,000 people between the ages of 15 and 39 are diagnosed with cancer, approximately 8 times more than children under age 15. This population faces a variety of unique short- and long-term health and psychosocial issues, such as difficulty reentering school, the workforce, or the dating scene; problems with infertility; cardiac, pulmonary, or other treatment repercussions; and secondary malignancies. Survivors are also at increased risk for psychiatric conditions such as anxiety, depression, substance abuse, and suicide and may have difficulty acquiring health insurance and paying for needed care. Identifying and Addressing the Needs of Adolescents and Young Adults with Cancer discusses a variety of topics important to adolescent and young adult patients with cancer, including the ways in which cancers affecting this group differ from cancers in other age groups and what that implies about the best treatments for these cancer patients. This report identifies gaps and challenges in providing optimal care to adolescent and young adult patients with cancer and to discuss potential strategies and actions to address them.
Keywords: Health and Medicine

Leveraging Culture to Address Health Inequalities: Examples from Native Communities: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
Leveraging Culture to Address Health Inequalities: Examples from Native Communities is the summary of a workshop convened in November 2012 by the Roundtable on the Promotion of Health Equity and the Elimination of Health Disparities of the Institute of Medicine. The workshop brought together more than 100 health care providers, policy makers, program administrators, researchers, and Native advocates to discuss the sizable health inequities affecting Native American, Alaska Native, First Nation, and Pacific Islander populations and the potential role of culture in helping to reduce those inequities. This report summarizes the presentations and discussion of the workshop and includes case studies that examine programs aimed at diabetes prevention and management and cancer prevention and treatment programs. In Native American tradition, the medicine wheel encompasses four different components of health: physical, emotional, mental, and spiritual. Health and well-being require balance within and among all four components. Thus, whether someone remains healthy depends as much on what happens around that person as on what happens within. Leveraging Culture to Address Health Inequalities addresses the broad role of culture in contributing to and ameliorating health inequities.
Keywords: Health and Medicine

Improving the Health, Safety, and Well-Being of Young Adults: Workshop Summary - Institute of Medicine; National Research Council (The National Academies Press, 2013)
Young adults are at a significant and pivotal time of life. They may seek higher education, launch their work lives, develop personal relationships and healthy habits, and pursue other endeavors that help set them on healthy and productive pathways. However, the transition to adulthood also can be a time of increased vulnerability and risk. Young adults may be unemployed and homeless, lack access to health care, suffer from mental health issues or other chronic health conditions, or engage in binge drinking, illicit drug use, or driving under the influence. Young adults are moving out of the services and systems that supported them as children and adolescents, but adult services and systems—for example, the adult health care system, the labor market, and the justice system—may not be well suited to supporting their needs. Improving the Health, Safety, and Well-Being of Young Adults is the summary of a workshop hosted by the Board on Children, Youth, and Families of the Institute of Medicine (IOM) and the National Research Council (NRC) in May, 2013. More than 250 researchers, practitioners, policy makers, and young adults presented and discussed research on the development, health, safety, and well-being of young adults. This report focuses on the developmental characteristics and attributes of this age group and its placement in the life course; how well young adults function across relevant sectors, including, for example, health and mental health, education, labor, justice, military, and foster care; and how the various sectors that intersect with young adults influence their health and well-being. Improving the Health, Safety, and Well-Being of Young Adults provides an overview of existing research and identifies research gaps and issues that deserve more intensive study. It also is meant to start a conversation aimed at a larger IOM/NRC effort to guide research, practices, and policies affecting young adults.
Keywords: Health and Medicine

Environmental Decisions in the Face of Uncertainty - Institute of Medicine (The National Academies Press, 2013)
The U.S. Environmental Protection Agency (EPA) is one of several federal agencies responsible for protecting Americans against significant risks to human health and the environment. As part of that mission, EPA estimates the nature, magnitude, and likelihood of risks to human health and the environment; identifies the potential regulatory actions that will mitigate those risks and protect public health1 and the environment; and uses that information to decide on appropriate regulatory action. Uncertainties, both qualitative and quantitative, in the data and analyses on which these decisions are based enter into the process at each step. As a result, the informed identification and use of the uncertainties inherent in the process is an essential feature of environmental decision making. EPA requested that the Institute of Medicine (IOM) convene a committee to provide guidance to its decision makers and their partners in states and localities on approaches to managing risk in different contexts when uncertainty is present. It also sought guidance on how information on uncertainty should be presented to help risk managers make sound decisions and to increase transparency in its communications with the public about those decisions. Given that its charge is not limited to human health risk assessment and includes broad questions about managing risks and decision making, in this report the committee examines the analysis of uncertainty in those other areas in addition to human health risks. Environmental Decisions in the Face of Uncertainty explains the statement of task and summarizes the findings of the committee.
Keywords: Environment and Environmental Studies; Policy for Science and Technology

Health Literacy: Improving Health, Health Systems, and Health Policy Around the World: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
The roots of health literacy can be traced back to the national literacy movement in India under Gandhi and to aid groups working in Africa to promote education and health. The term health literacy was first used in 1974 and described as "health education meeting minimal standards for all school grade levels". From that first use the definition of health literacy evolved during the next 30 years with official definitions promulgated by government agencies and large programs. Despite differences among these definitions, they all hold in common the idea that health literacy involves the need for people to understand information that helps them maintain good health. Although the United States produces a majority of the research on health literacy, Europe has strong multinational programs as well as research efforts, and health literacy experts in developing countries have created successful programs implemented on a community level. Given these distinct strengths of efforts worldwide, there are many opportunities for collaboration. International collaboration can harness the United States' research power, Europe's multilingual and multinational experience, and developing nations' community-based programs to create robust programs and research that reach people—not based on language or nationality but on need and value. A workshop on international health literacy efforts that feature presentations and discussion about health literacy interventions from various countries as well as other topics related to international health literacy was held as the basis for this report. Health Literacy: Improving Health, Health Systems, and Health Policy Around the World summarizes the findings and discussions at the workshop.
Keywords: Health and Medicine

Substance Use Disorders in the U.S. Armed Forces - Institute of Medicine (The National Academies Press, 2013)
Problems stemming from the misuse and abuse of alcohol and other drugs are by no means a new phenomenon, although the face of the issues has changed in recent years. National trends indicate substantial increases in the abuse of prescription medications. These increases are particularly prominent within the military, a population that also continues to experience long-standing issues with alcohol abuse. The problem of substance abuse within the military has come under new scrutiny in the context of the two concurrent wars in which the United States has been engaged during the past decade—in Afghanistan (Operation Enduring Freedom) and Iraq (Operation Iraqi Freedom and Operation New Dawn). Increasing rates of alcohol and other drug misuse adversely affect military readiness, family readiness, and safety, thereby posing a significant public health problem for the Department of Defense (DoD). To better understand this problem, DoD requested that the Institute of Medicine (IOM) assess the adequacy of current protocols in place across DoD and the different branches of the military pertaining to the prevention, screening, diagnosis, and treatment of substance use disorders (SUDs). Substance Use Disorders in the U.S. Armed Forces reviews the IOM's task of assessing access to SUD care for service members, members of the National Guard and Reserves, and military dependents, as well as the education and credentialing of SUD care providers, and offers specific recommendations to DoD on where and how improvements in these areas could be made.
Keywords: Health and Medicine; Conflict and Security Issues

Public Health Linkages with Sustainability: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
In 1992 world leaders met at the Earth Summit in Rio de Janeiro to reaffirm the Declaration of the United Nations Conference on the Human Environment that was established on June 16, 1972 in Stockholm. The meeting resulted in the adoption of Agenda 21 by the member states which is a framework for the transition to a more sustainable world. In 2012 the members gathered to assess and reaffirm the importance of progress towards the efforts of Agenda 21.
Keywords: Health and Medicine

Priorities for Research to Reduce the Threat of Firearm-Related Violence - Institute of Medicine; National Research Council (The National Academies Press, 2013)
In 2010, more than 105,000 people were injured or killed in the United States as the result of a firearm-related incident. Recent, highly publicized, tragic mass shootings in Newtown, CT; Aurora, CO; Oak Creek, WI; and Tucson, AZ, have sharpened the American public's interest in protecting our children and communities from the harmful effects of firearm violence. While many Americans legally use firearms for a variety of activities, fatal and nonfatal firearm violence poses a serious threat to public safety and welfare.
Keywords: Behavioral and Social Sciences; Health and Medicine

Evaluating Obesity Prevention Efforts: A Plan for Measuring Progress - Institute of Medicine (The National Academies Press, 2013)
Obesity poses one of the greatest public health challenges of the 21st century, creating serious health, economic, and social consequences for individuals and society. Despite acceleration in efforts to characterize, comprehend, and act on this problem, including implementation of preventive interventions, further understanding is needed on the progress and effectiveness of these interventions. Evaluating Obesity Prevention Efforts develops a concise and actionable plan for measuring the nation's progress in obesity prevention efforts—specifically, the success of policy and environmental strategies recommended in the 2012 IOM report Accelerating Progress in Obesity Prevention: Solving the Weight of the Nation. This book offers a framework that will provide guidance for systematic and routine planning, implementation, and evaluation of the advancement of obesity prevention efforts. This framework is for specific use with the goals and strategies from the 2012 report and can be used to assess the progress made in every community and throughout the country, with the ultimate goal of reducing the obesity epidemic. It offers potentially valuable guidance in improving the quality and effect of the actions being implemented. The recommendations of Evaluating Obesity Prevention Efforts focus on efforts to increase the likelihood that actions taken to prevent obesity will be evaluated, that their progress in accelerating the prevention of obesity will be monitored, and that the most promising practices will be widely disseminated.
Keywords: Food and Nutrition; Health and Medicine

Sodium Intake in Populations: Assessment of Evidence - Institute of Medicine (The National Academies Press, 2013)
Despite efforts over the past several decades to reduce sodium intake in the United States, adults still consume an average of 3,400 mg of sodium every day. A number of scientific bodies and professional health organizations, including the American Heart Association, the American Medical Association, and the American Public Health Association, support reducing dietary sodium intake. These organizations support a common goal to reduce daily sodium intake to less than 2,300 milligrams and further reduce intake to 1,500 mg among persons who are 51 years of age and older and those of any age who are African-American or have hypertension, diabetes, or chronic kidney disease. A substantial body of evidence supports these efforts to reduce sodium intake. This evidence links excessive dietary sodium to high blood pressure, a surrogate marker for cardiovascular disease (CVD), stroke, and cardiac-related mortality. However, concerns have been raised that a low sodium intake may adversely affect certain risk factors, including blood lipids and insulin resistance, and thus potentially increase risk of heart disease and stroke. In fact, several recent reports have challenged sodium reduction in the population as a strategy to reduce this risk. Sodium Intake in Populations recognizes the limitations of the available evidence, and explains that there is no consistent evidence to support an association between sodium intake and either a beneficial or adverse effect on most direct health outcomes other than some CVD outcomes (including stroke and CVD mortality) and all-cause mortality. Some evidence suggested that decreasing sodium intake could possibly reduce the risk of gastric cancer. However, the evidence was too limited to conclude the converse—that higher sodium intake could possibly increase the risk of gastric cancer. Interpreting these findings was particularly challenging because most studies were conducted outside the United States in populations consuming much higher levels of sodium than those consumed in this country. Sodium Intake in Populations is a summary of the findings and conclusions on evidence for associations between sodium intake and risk of CVD-related events and mortality.
Keywords: Food and Nutrition

Guidebook for Developing Subnational Commodity Flow Data - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2013)
TRB’s National Cooperative Freight Research Program (NCFRP) Report 26: Guidebook for Developing Subnational Commodity Flow Data explores how state departments of transportation and other subnational agencies can obtain and compile commodity flow data.The Guidebook contains descriptions of existing public and private commodity flow data; standard procedures for compiling local, regional, state, and corridor databases from these commodity flow data sources; procedures and methodologies for conducting subnational commodity flow surveys and studies; and methods for using commodity flow data in local, regional, state, and corridor practice.In addition to the Guidebook, two subtask reports from NCFRP Project 20--Review of Subnational Commodity Flow Data Development Efforts and National Freight-Related Data Sets and Demonstration of Application of Establishment Survey--are available only in electronic format.
Keywords: Transportation and Infrastructure

Creating Equal Opportunities for a Healthy Weight: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
Creating Equal Opportunities for a Healthy Weight is the summary of a workshop convened by the Institute of Medicine's Standing Committee on Childhood Obesity Prevention in June 2013 to examine income, race, and ethnicity, and how these factors intersect with childhood obesity and its prevention. Registered participants, along with viewers of a simultaneous webcast of the workshop, heard a series of presentations by researchers, policy makers, advocates, and other stakeholders focused on health disparities associated with income, race, ethnicity, and other characteristics and on how these factors intersect with obesity and its prevention. The workshop featured invited presentations and discussions concerning physical activity, healthy food access, food marketing and messaging, and the roles of employers, health care professionals, and schools. The IOM 2012 report Accelerating Progress in Obesity Prevention acknowledged that a variety of characteristics linked historically to social exclusion or discrimination, including race, ethnicity, religion, socioeconomic status, gender, age, mental health, disability, sexual orientation or gender identity, geographic location, and immigrant status, can thereby affect opportunities for physical activity, healthy eating, health care, work, and education. In many parts of the United States, certain racial and ethnic groups and low-income individuals and families live, learn, work, and play in places that lack health-promoting resources such as parks, recreational facilities, high-quality grocery stores, and walkable streets. These same neighborhoods may have characteristics such as heavy traffic or other unsafe conditions that discourage people from walking or being physically active outdoors. The combination of unhealthy social and environmental risk factors, including limited access to healthy foods and opportunities for physical activity, can contribute to increased levels of chronic stress among community members, which have been linked to increased levels of sedentary activity and increased calorie consumption. Creating Equal Opportunities for a Healthy Weight focuses on the key obesity prevention goals and recommendations outlined in Accelerating Progress in Obesity Prevention through the lens of health equity. This report explores critical aspects of obesity prevention, while discussing potential future research, policy, and action that could lead to equity in opportunities to achieve a healthy weight.
Keywords: Food and Nutrition

Critical Aspects of EPA's IRIS Assessment of Inorganic Arsenic: Interim Report - National Research Council (The National Academies Press, 2013)
The US Environmental Protection Agency (EPA) Integrated Risk Information System (IRIS) program develops toxicologic assessments of environmental contaminants. IRIS assessments provide hazard identification and dose-response assessment information. The information is then used in conjunction with exposure information to characterize risks to public health and may be used in risk-based decisionmaking, in regulatory actions, and for other risk-management purposes. Since the middle 1990s, EPA has been in the process of updating the IRIS assessment of inorganic arsenic. In response to a congressional mandate for an independent review of the IRIS assessment of inorganic arsenic, EPA requested that the National Research Council convene a committee to conduct a two-phase study. Critical Aspects of EPA's IRIS Assessment of Inorganic Arsenic is the report of the first phase of that study. This report evaluates critical scientific issues in assessing cancer and noncancer effects of oral exposure to inorganic arsenic and offers recommendations on how the issues could be addressed in EPA's IRIS assessment.
Keywords: Environment and Environmental Studies

Oral Health Literacy: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
The Institute of Medicine (IOM) Roundtable on Health Literacy focuses on bringing together leaders from the federal government, foundations, health plans, associations, and private companies to address challenges facing health literacy practice and research and to identify approaches to promote health literacy in both the public and private sectors. The roundtable serves to educate the public, press, and policy makers regarding the issues of health literacy, sponsoring workshops to discuss approaches to resolve health literacy challenges. It also builds partnerships to move the field of health literacy forward by translating research findings into practical strategies for implementation. The Roundtable held a workshop March 29, 2012, to explore the field of oral health literacy. The workshop was organized by an independent planning committee in accordance with the procedures of the National Academy of Sciences. The planning group was composed of Sharon Barrett, Benard P. Dreyer, Alice M. Horowitz, Clarence Pearson, and Rima Rudd. The role of the workshop planning committee was limited to planning the workshop. Unlike a consensus committee report, a workshop summary may not contain conclusions and recommendations, except as expressed by and attributed to individual presenters and participants. Therefore, the summary has been prepared by the workshop rapporteur as a factual summary of what occurred at the workshop.
Keywords: Health and Medicine

Measuring What We Spend: Toward a New Consumer Expenditure Survey - National Research Council (The National Academies Press, 2013)
The Consumer Expenditure (CE) surveys are the only source of information on the complete range of consumers' expenditures and incomes in the United States, as well as the characteristics of those consumers. The CE consists of two separate surveys: (1) a national sample of households interviewed five times at three-month intervals; and (2) a separate national sample of households that complete two consecutive one-week expenditure diaries. For more than 40 years, these surveys, the responsibility of the Bureau of Labor Statistics (BLS), have been the principal source of knowledge about changing patterns of consumer spending in the U.S. population. In February 2009, BLS initiated the Gemini Project, the aim of which is to redesign the CE surveys to improve data quality through a verifiable reduction in measurement error with a particular focus on underreporting. The Gemini Project initiated a series of information-gathering meetings, conference sessions, forums, and workshops to identify appropriate strategies for improving CE data quality. As part of this effort, BLS requested the National Research Council's Committee on National Statistics (CNSTAT) to convene an expert panel to build on the Gemini Project by conducting further investigations and proposing redesign options for the CE surveys. The charge to the Panel on Redesigning the BLS Consumer Expenditure Surveys includes reviewing the output of a Gemini-convened data user needs forum and methods workshop and convening its own household survey producers workshop to obtain further input. In addition, the panel was tasked to commission options from contractors for consideration in recommending possible redesigns. The panel was further asked by BLS to create potential redesigns that would put a greater emphasis on proactive data collection to improve the measurement of consumer expenditures. Measuring What We Spend summarizes the deliberations and activities of the panel, discusses the conclusions about the uses of the CE surveys and why a redesign is needed, as well as recommendations for the future.
Keywords: Industry and Labor; Behavioral and Social Sciences; Surveys and Statistics

Health and Incarceration: A Workshop Summary - Institute of Medicine; National Research Council (The National Academies Press, 2013)
Over the past four decades, the rate of incarceration in the United States has skyrocketed to unprecedented heights, both historically and in comparison to that of other developed nations. At far higher rates than the general population, those in or entering U.S. jails and prisons are prone to many health problems. This is a problem not just for them, but also for the communities from which they come and to which, in nearly all cases, they will return. Health and Incarceration is the summary of a workshop jointly sponsored by the National Academy of Sciences(NAS) Committee on Law and Justice and the Institute of Medicine(IOM) Board on Health and Select Populations in December 2012. Academics, practitioners, state officials, and nongovernmental organization representatives from the fields of healthcare, prisoner advocacy, and corrections reviewed what is known about these health issues and what appear to be the best opportunities to improve healthcare for those who are now or will be incarcerated. The workshop was designed as a roundtable with brief presentations from 16 experts and time for group discussion. Health and Incarceration reviews what is known about the health of incarcerated individuals, the healthcare they receive, and effects of incarceration on public health. This report identifies opportunities to improve healthcare for these populations and provides a platform for visions of how the world of incarceration health can be a better place.
Keywords: Behavioral and Social Sciences; Health and Medicine